Nowa ewangelizacja w służbie przekazu prawd wiary chrześcijańskiej - Broński, Włodzimierz (Studia Pastoralne, 2026)
The new evangelization is dialogical and mystagogical. It is a fundamental task of every ecclesial community. In our time it is done in a pluralistic society primarily through the preaching of the word of God from person to person and the witness of a Christian life. Its objectives are faith, conversion of every man, bringing man to salvation. Bearing in mind the situation of the Christian faith in the modern world, one ought to seek new forms of preaching the word of God, especially using the electronic media.